From e-Lexicography to Electronic Lexicography. A Joint Review - Caruso, Valeria (Lexikos, 2013)
Two recently published books outline the main issues of the current debate on lexicography. The first, e-Lexicography edited by Fuertes-Olivera and Bergenholtz in 2011, presents the standpoints of the lexicographical function theory on the future developments of dictionaries, while, in some chapters, current innovative tools are described, tools which allow customizations according to the user's type of need. The second volume, Electronic Lexicography edited by Granger and Paquot in 2012, presents different opposing views on what the dictionaries of the future will look like, such as the linguistic-oriented stance of Hanks and that of Tarp concerning theoretical lexicography. The dictionary projects that are described within these pages offer an interesting basis of comparison with those developed by the representatives of the function theory. Keywords: computer assisted language learning (call), corpus linguistics, customization, databases, dictionary survey, dictionary use, efficacy, efficiency, electronic lexicography, information science, languages for special purposes, lexicographical function theory, linguistic theory, monofunctional dictionary, p-dictionaries, practical lexicography, usability testing